Correlation between OSAHS and Early Peripheral Atherosclerosis Indices in Patients with Type 2 Diabetes Mellitus in China: A Cross-Sectional Inpatient Study - Xin Zhao; Xiaofeng Yu; Sixu Xin; Wei Zhang; Xiaomei Zhang; Linong Ji (Journal of Diabetes Research)
Objective: To analyze the differences of early atherosclerosis indices in type 2 diabetes mellitus (T2DM) patients with different degrees of obstructive sleep apnea-hypopnea syndrome (OSAHS) and explore the correlation between them, so as to provide a new clinical basis for the prevention and treatment of early atherosclerosis in patients with T2DM and OSAHS. Methods. A prospective study was conducted in 312 patients with T2DM and snoring who were hospitalized in the Department of Endocrinology, Peking University International Hospital from January 2017 to January 2020. According to the monitoring results, 312 patients were divided into 4 groups including the control group (208 cases), mild OSAHS group (18 cases), moderate OSAHS group (38 cases), and severe OSAHS group (48 cases). Multivariate logistic regression analysis was used to analyze the early atherosclerosis indices including brachial-ankle pulse wave velocity (PWV) and ankle-brachial index (ABI) in patients with T2DM coexistence with different degrees of OSAHS. Results. (1) As the degree of OSAHS increased, ABI decreased gradually and was lower than that in the control group, but PWV increased and was higher than that in the control group (p<0.05, respectively). (2) The apnea-hypopnea index (AHI) positively correlated with PWV (r=0.36, p<0.05) and negatively correlated with ABI (r=−0.37, p<0.05). (3) Multivariate logistic regression showed that after adjusting for age, gender, duration, BMI, blood pressure, blood glucose, blood lipid, and other factors, OSAHS was a risk factor of lower extremity arterial disease (LEAD) in patients with T2DM. With the increase of degree of OSAHS, the risk of lower extremity atherosclerosis gradually increased. Conclusion. OSAHS is an independent risk factor of LEAD in patients with T2DM, and with the increase of AHI, the ABI and PWV have changed, which provides a new clinical basis for the prevention and the treatment of early atherosclerosis in patients with T2DM and OSAHS.